Tanggapan Beberapa Varietas Kedelai terhadap Budidaya Basah di Entisol = Response of soybean cultivars to saturated soil culture in Entisol - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Soybean acclimated and grew well under saturated soil culture. Saturated soil culture conditions were established by planting soybean on raised bed and applying furrow irrigation continuously to allow saturation but not flooding. Saturated soil culture increased growth and yield of soybean. An experiment to study the response of ten soybean cultivars to saturated soil culture was carried out in glass house, Research Institute for Legumes and Tuber Crops, Malang from March to September 2002. A split plot design was used with three replications. Main plot was irrigation treatments consisted of conventional culture, which was irrigated 2-4 days and saturated soil culture (controlled waterloggings with water level in the box 15 cm below soil surface). Sub plot was soybean cultivars consisted of early cultivars (70-75 days of maturity) Malabar, Tidar, and Lokon